Oryza sativa L دراسة تأثير الجهد الاليلوباثي للمستخلصات المائية والكحولية لأوراق نباتي السلهو والسعد في انبات ونمو بعض الادغال المرافقة لنمو نبات الرز. - كوثر كاظم عبد الرضا; علي ياسر حافظ العيساوي; حوراء غسان حسين (مجلة علوم ذي قار, 2019)
This experment was carried out in the Season (2014 - 2015) to assess The inhibtory activity of plants Paspalum distichum L., and Cyperus spp. L.. Water and alkhol extracts on germination and growth of Cyperus odoratus L., Diplanche fusca Beaur (L.). and Echinocholoa crus-galli L. Seeds of the test plants Culturing in petridishes then treated with water and alkehol extracts at concentrations of (0%, 40%, 60% 80% and 100%) .Plant extracts showed a significant reduction of germination percentage, velocity coefficient of germination, shoots and roots length and their dry weight, of all test species; principally on the increased concentration till 100%; except the low concentrations were markediy Stimulated in shoots length, shoots and roots dry weight in Cyperusodoratus L. coefficient velocity of germination, shoots length in Medicago hispida L., shoots length in Sonchus oleraceus L